Quantitative analysis of the dominant external factors influencing elite speed Skaters' performance using BP neural network - Yang, Z.; Ke, P.; Zhang, Y.; Du, F.; Hong, P. (Frontiers in Sports and Active Living, 2024)
Introduction Speed skating, being a popular winter sport, imposes significant demands on elite skaters, necessitating their effective assessment and adaptation to diverse environmental factors to achieve optimal race performance.